Acceptance Research on The Adaptation of Target Audience Personas in Graphic Design - Goh, Chu Hiang (Advances in Social Sciences Research Journal, 2020)
Target Audience Personas (TAP) is a new target audience study method for the graphic design process which adopted from the user personas in information studies. The goal of the TAP is to facilitate graphic designer to understand the behaviour and attitude of their target audience in a more profound level to create design outcomes which can evolve the affordance and behavioural change. Personas allow designer engaged in empathy process whereby they can design according to the needs and preferences of the target audiences. In order to explore the acceptance of designers to the TAP in the design process, acceptance research based on the Technology Acceptance Model (TAM) was conducted. A group of design students who engaged TAP in their design projects has participated in the study. The result showed that majority of the students consider TAP is useful and easy to use. They anticipate using TAP in their future design career endeavour.